Scenarios for writing : issues, analysis, and response - Glau, Gregory R.; Jacobsen, Craig B. (Boston : New York : McGraw Hill, 2001)
A rhetoric-reader that presents six scenarios rooted in controversies that dramatize rhetorical issues and engage students in conversations informed by competing points of view.
Includes bibliographical references and index.
Keywords: English language -- Rhetoric; Narration (Rhetoric); Report writing